‘Tenebricosus’ and Irony in Catull. 3 - Kotova, Anastasia (Hyperboreus, 2013)
The author investigates semantics of Latin tenebricosus and its various connotations. She argues against D. F. S. Thomson’s assertion that tenebricosus in Cat. 3, 11 has colloquial character, which lends to the poem a degree of parody.